2009
DOI: 10.1007/s00244-009-9373-0
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Sublethal Effects of Embryonic and Larval Exposure of Hyla versicolor to Stormwater Pond Sediments

Abstract: Stormwater ponds are common features of modern stormwater management practices. Stormwater ponds often retain standing water for extended periods of time, develop vegetative characteristics similar to natural wetlands, and attract wildlife. However, because stormwater ponds are designed to capture pollutants, wildlife that utilize ponds might be exposed to pollutants and suffer toxicological effects. To investigate the toxicity of stormwater pond sediments to Hyla versicolor, an anuran commonly found using ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 28 publications
3
41
0
1
Order By: Relevance
“…Our study joins a small but growing literature base that highlights changes in time to and size at metamorphosis among tadpoles exposed to road salts. Brand et al (2010) observed the same trends in faster time to and larger size at metamorphosis among gray treefrogs developing in stormwater pond sediments with elevated Cl − levels. Chinathamby et al (2006) reported an increase in mass at metamorphosis among brown treefrogs (Litoria ewingii) exposed to low and moderate concentrations of sea salts.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Our study joins a small but growing literature base that highlights changes in time to and size at metamorphosis among tadpoles exposed to road salts. Brand et al (2010) observed the same trends in faster time to and larger size at metamorphosis among gray treefrogs developing in stormwater pond sediments with elevated Cl − levels. Chinathamby et al (2006) reported an increase in mass at metamorphosis among brown treefrogs (Litoria ewingii) exposed to low and moderate concentrations of sea salts.…”
Section: Discussionsupporting
confidence: 73%
“…Much like zooplankton and algae, chloride salt effects on anurans are likely to be species-specific and dependent upon life history as well as environmental factors such as water chemistry and temperature (Brand et al 2010). Our study joins a small but growing literature base that highlights changes in time to and size at metamorphosis among tadpoles exposed to road salts.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This study was designed to be sublethal to gray treefrog ( Hyla versicolor ) larvae; therefore, the higher chloride concentration used reflected the uppermost limit for successful embryonic and larval survival as determined by Brand et al [31]. The stormwater ponds used to collect inoculum were representative of those in Red Run Watershed that can support successful amphibian development and survival [23].…”
Section: Methodsmentioning
confidence: 99%